AN INTERNATIONAL STUDY ON DIFFERENT FACTORS OF OPERATING SCHOOL TEMPORARY POSITION: FOCUSING ON CASES OF KOREA, HOLLAND, GERMANY, SWEDEN - Jung, Dae (PEOPLE: International Journal of Social Sciences, 2017)
The necessities of strategies for the labor force in the school temporary position are superior in education practice. In the perspective of government, a new paradigm and method for them such as employment stability, better treatment and fewer tasks have been sought. However, the information for them is not enough. While seeing the main issue to manage an temporary workers and the feature of the system for them in schools of Holland, Germany and Sweden, this study shows an effective plan for not only the labor force in the school temporary workers and but their skill development. Based on the result of a plan in education office, supporting office, and schools this study proposes the political and institutional method to revitalize the efficient management of temporary workers in school.